Cabaret on the gears of the Machine City (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper presents the intersection of temporalities and the remapping of the process of urban occupation developed during the making of Cabaret Macchina - uma pós-ópera anti-edipiana Casa Selvática. The imagery of the weed, those small unwanted plants that grow between concrete blocks along the city, unfold as a poetic-visual, The cabaret emerges from the underground to everyday life, taking place at public spaces in broad day light. To flow rate branches at such odd vegetation, blended it here the narration from three creators, but united as an only one lecturer in order to move the pieces, and blurring the margins between gears from this cabaret machine.
Keywords: Cabaret; Collective; Processual Art; Precariousness; Public spaces